Analisis Dampak Pendampingan Pelaporan SPT terhadap Kepatuhan Wajib Pajak Orang Pribadi - Rahmadini, Sheila Rosy; Baldan, Ulyaa Zidni; Ayu, Diyan Putri (Jurnal Antologi Hukum, 2025)
The high level of awareness regarding compliance in paying taxes is an important part of the Directorate General of Taxes' strategy to increase state revenue, which will ultimately benefit society. Therefore, it is necessary to provide assistance to the general public who are subject to taxation in reporting their tax returns, so that compliance with individual income tax payments can be achieved. The purpose of this study is to analyze and examine the impact of annual tax return reporting assistance on the compliance level of individual taxpayers in fulfilling their tax obligations, particularly in the context of implementing the Self-Assessment System in Indonesia. The method used in this research is a literature review or library research using a descriptive qualitative approach, where the study utilizes books, journals, and written media sources as reference materials. The results of this study, namely the assistance in reporting tax returns, which is a public service, have successfully achieved good service quality. This is because the mentoring activities have received satisfaction from the taxpayers. The assistance provided by tax volunteers in filing tax returns has a positive impact on taxpayers. With the help of the volunteers, taxpayers are able to fulfilll their obligations and rights in accordance with applicable regulations. Assisting with SPT reporting also has a positive and significant impact on the level of compliance among individual taxpayers.